2020
DOI: 10.3389/fmicb.2020.598010
|View full text |Cite
|
Sign up to set email alerts
|

Streptococcus thermophilus Attenuates Inflammation in Septic Mice Mediated by Gut Microbiota

Abstract: Sepsis is a life-threatening organ dysfunction condition caused by a dysregulated host response to infection and lack of effective treatment method. Supplementation of probiotics has emerged as a potential biotherapy for inflammatory diseases in recent years, but its role in protecting viscera against the damage caused by sepsis and the underlying mechanism is poorly understood. Streptococcus thermophilus 19 is one of the most well-studied probiotics, which is selected in this study among seven strains isolate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 37 publications
1
20
0
Order By: Relevance
“…Examination of the fecal microbiota showed increases in S. thermophilus and L. lactis with antibiotic administration, with a corresponding reduction in spasms. These microbes are also known to exert psychotropic effects by regulating brain activity and reducing inflammation (28,29). Likewise, maternal exposure of L. lactis reduced anxiety-like behavior and improved the development of cortical architecture in mice, which may be involved in immunological regulation by the microbe (30).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Examination of the fecal microbiota showed increases in S. thermophilus and L. lactis with antibiotic administration, with a corresponding reduction in spasms. These microbes are also known to exert psychotropic effects by regulating brain activity and reducing inflammation (28,29). Likewise, maternal exposure of L. lactis reduced anxiety-like behavior and improved the development of cortical architecture in mice, which may be involved in immunological regulation by the microbe (30).…”
Section: Discussionmentioning
confidence: 99%
“…lactis with antibiotic administration, with a corresponding reduction in spasms. These microbes are also known to exert psychotropic effects by regulating brain activity and reducing inflammation ( 28 , 29 ). Likewise, maternal exposure of L .…”
Section: Discussionmentioning
confidence: 99%
“…As in a previous study 29 , we recovered Streptococcus thermophilus from fecal metagenomic samples of adult allo-HCT recipients. S. thermophilus is generally not considered as a pathogen and is a commercially available probiotic that has been reported to attenuate inflammation 41 . Our findings do not formally exclude the possibility that translocated oral bacteria may exert pathologic effects in the intestine, even when present at low absolute levels.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the administration of Lactobacillus cocktails has been reported to increase microbiota diversity post-antibiotic treatment [ 44 , 45 ]. Additionally, it has been reported that LPS-induced decreases in gut microbiota diversity in a mouse model was restored by a single strain of S. thermophilus [ 46 ]. Combining two Lactobacillus strains and S. thermophilus also improved the microbiota diversity in neonatal piglets [ 47 ].…”
Section: Discussionmentioning
confidence: 99%